Reusing Construction and Demolition Waste to Prepare Alkali-Activated Cement - Borrachero, Maria; Paya, Jordi; Brito, Santiago; Segura Sierpe, Yasna Pamela; Soriano, Lourdes; Tashima, Mauro M.; Maria Monzo, Jose (My University, 2022)
Large amounts of waste are derived not only from construction processes, but also the demolition of existing buildings. Such waste occupies large volumes in landfills, which makes its final disposal difficult and expensive. Reusing this waste type is generally limited to being employed as filler material or recycled aggregate in concrete, which limits its valorisation. The present work proposes reusing construction and demolition waste to manufacture alkali-activated cement to improve its sustainability and recovery. Construction and demolition waste (C&DW) from a demolition waste collection plant in Valencia (Spain) was physically and chemically characterised. This residue contained large fractions of concrete, mortar, bricks, and other ceramic materials. X-ray fluorescence (XRF) analysis showed that its chemical composition was mainly CaO, SiO2 and Al2O3. X-ray diffraction (XRD) analysis revealed that it presented some crystalline products, and quartz (SiO2) and calcite (CaCO3) were the main components. Blends of C&DW and blast furnace slag (BFS) were alkali-activated with mixtures of sodium hydroxide and sodium silicate. The corresponding pastes were characterised by techniques such as thermogravimetry and scanning electron microscopy (SEM). The alkali-activated mortars were prepared, and the resulting mortars' compressive strength was determined, which was as high as 58 MPa with the 50% C&DW-50% BFS mixture. This work concluded that it is possible to make new sustainable binders by the alkali activation of C&DW-BFS without using Portland cement.
Keywords: valorisation; construction and demolition waste; blast furnace slag; compressive strength; microstructure